Combination of ultrasound‐assisted ethyl chloroformate derivatization and switchable solvent liquid‐phase microextraction for the sensitive determination of l‐methionine in human plasma by GC–MS. Issue 6 (8th January 2020) - Erarpat, Sezin; Bodur, Süleyman; Öztürk Er, Elif; Bakırdere, Sezgin
Abstract: A green and fast analytical method for the determination of l ‐methionine in human plasma is presented in this study. Preconcentration of the analyte was carried out by switchable solvent liquid phase microextraction after ethyl chloroformate derivatization reaction. Instrumental detection of the analyte was performed by means of gas chromatography–mass spectrometry. N, N ‐Dimethyl benzylamine was used in the synthesis of switchable solvent. Protonated N, N ‐dimethyl benzylamine volume, volume/concentration of sodium hydroxide, and vortex period were meticulously fixed to their optimum values. Besides, ethyl chloroformate, pyridine, and ethanol volumes were optimized in order to get high derivatization yield. After the optimization studies, limit of detection and quantitation values were attained as 3.30 and 11.0 ng/g, respectively, by the developed switchable solvent liquid phase microextraction gas chromatography–mass spectrometry method that corresponding to 76.7‐folds enhancement in detection power of the gas chromatography–mass spectrometry system. Applicability and accuracy of the switchable solvent liquid phase microextraction–gas chromatography–mass spectrometry method were also checked by spiking experiments. Percent recovery results were ranged from 97.8 to 100.5% showing that human plasma samples could be analyzed for its l ‐methionine level by the proposed method.